A biopirataria e a apropriação dos conhecimentos tradicionais associados à biodiversidade da Amazônia Brasileira - Alencar, Aline Ferreira de (2008)
The biopiracy is a non authorized appropriation of certain region genetic patrimony, including fauna, flora, microorganisms and traditional knowledge associated to biodiversity. This kind of activity happens in developing countries, including Brasil, especially in the Brazilian Amazon, region rich in biodiversity, that attracts the lust for natural sources, by countries with technology, however poor in biodiversity, who intends to manufacturate new products, obtaining great financial returns. Therefore the nature is seen like raw material, source of capital gains. In this context, the appropriation of the traditional knowledge associated to biodiversity, from the Indians people and traditional populations, depicts a powerful short cut to create new products, because using the bioprospection is possible to reach the good results with economic rationality. The biopiracy attempts against the national interest and human rights, for that reason there is a suggestion to punish this activity by the criminal law, considering the relevance of the object, the environment. Also, to curb on biopiracy, there is also a necessity to improve the surveillance in the Brazilian Amazon, investment in research, and the application of the information, education and environmental participation principles, as a way of combining the State and collectivity, to prevent this harmful activity to Brazil and the traditional knowledge keepers. Keys-words: Biopiracy. Traditional knowledge biodiversity related. Brazilian Amazon. Genetic patrimony.